EDUCATION IN KASTAMONU ACCORDING TO EDUCATION YEARBOOKS AND PROVINCE YEARBOOKS (1869-1903) - Sağlam, Tarık; Çiydem, Erol (Uluslararasi Sosyal Bilgilerde Yeni Yaklasimlar Dergisi (IJONASS), 2024)
Yearbooks, which are first-hand sources, are important for obtaining information about the Ottoman education system. This study aims to reveal the educational status in Kastamonu province between 1869 and 1903, which aligns with the data in the Kastamonu Provincial Yearbooks and Education Yearbooks. The first publication of the Kastamonu Provincial Yearbook was in 1869, and the last was in 1903. Education Yearbooks were published between 1899 and 1903. It is known that Kastamonu provincial yearbooks were not published every year. Although they occur at different intervals, twenty-one Kastamonu Provincial Yearbooks and five Education Yearbooks, excluding the Education Yearbook of 1902, are the main data sources in the study. Data in the study was collected using the document review method and subjected to descriptive analysis. Historical research was used as the study method. In the years examined, educational institutions understood to exist in Kastamonu province are primary schools, middle schools, high schools, industrial schools, and schools for non-Muslims. The change in the number of students and teachers in educational institutions over the years is also among the study's important findings.